Tinjauan dan Analisis Hukum Tentang Pembagian Harta Usaha Bersama Dalam Perkawinan - Sahid, Syarifuddin (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2025)
Many marriages end in divorce, and issues regarding joint assets often arise between ex-husbands and ex-wives. The type of research used is descriptive qualitative. The approach method in this research is a normative legal approach. Respondents in the research were the divorce perpetrators and judges at the Klaten Religious Court and the Surakarta District Court. The conclusions in this research are: (1) similarities when filing a lawsuit for joint assets from the Religious Court and the District Court, that the division of joint assets in a marriage is carried out after a divorce decision is made. (2) The difference according to the KHI is based on Article 97, joint assets after divorce are divided equally, each ½ part between the husband and wife is the same. Meanwhile, according to the Civil Code, the division can be carried out based on evidence submitted by the plaintiff and defendant. (3) The basis for the judge's consideration in deciding the case of the division of joint assets according to the KHI is twofold, namely the basis of deliberation and justice.